Field observations as an indispensable tool for religious studies. - Olga Nedavnya (Українське Pелігієзнавство, 2014)
Among the rich instruments of religious studies, the fundamental place belongs to field observation. Only an in-depth study of religious life makes it possible for academics to have an adequate understanding of the phenomena of faith and of the Church, of spiritual and religious problems, of certain denominational features. Field research is not a substitute for something else. At the time of comprehension not only their essence, certain kinds and methods, but also the status of the researcher, which is occupied by them.